China’s Inventive Diplomatic Coercion: The Case of the Sino-Lithuanian Bilateral Relationship Crisis - Andrijauskas, Konstantinas; Boruta, Raigirdas (Politologija, 2025)
Since mid-2021, Lithuania has emerged on the receiving end of China’s unusually ferocious and multi-dimensional pressure campaign. The aim of this article is to comprehensively analyse those assertive measures that could be broadly defined as diplomacy-related and were employed by Beijing throughout the post-2018 decline of this bilateral relationship, especially its crisis phase. Based on an instrumental theoretical approach to foreign policy making embodied by the scholarship on statecraft in the international arena, this qualitative case study highlights the uniqueness and ingenuity of Chinese actions in this important but surprisingly overlooked domain. It thus offers a conceptual innovation that would allow for better research into similar diplomacy-related measures used elsewhere. The authors argue that the notion of ‘diplomatic coercion’ better encapsulates the variety and complexity of such foreign policy instruments employed by China or potentially any other resourceful country.